Photobioelectrochemistry of intact photosynthetic bacteria: Advances and future outlook - Torquato, Lilian Danielle de Moura [UNESP]; Grattieri, Matteo (Elsevier, 2022)
Over the past decade, increasing research focus has been posed on the use of intact and viable photosynthetic microorganisms in biohybrid electrochemical systems. Various works have shown that these biotic/abiotic photoelectrochemical systems can be utilized to develop biophotovoltaics, biosensing devices, and to perform light-driven bioelectrosynthesis. This Emerging Opinions article highlights the accomplishments achieved in the last three years in the photobioelectrochemistry of intact photosynthetic bacteria. Specifically, the new approaches utilized to shed light on the mechanisms at the basis of microbial photobioelectrochemistry are discussed, together with fascinating solutions to artificially tune the photo-induced extracellular electron transfer. The most recent groundbreaking achievements toward the practical application of biohybrid photoelectrochemical systems are also highlighted, before presenting a future outlook for intact photosynthetic bacteria photobioelectrochemistry.
Keywords: Bioelectrosynthesis; Biophotovoltaic; Biosensor; Microbial electrochemistry; Photo-induced extracellular electron transfer; Semi-artificial photosynthesis; Synthetic biology